Rancangan Strategi Pemasaran Layanan JIMS (Jabarlink Internet Managed Service) di Perhotelan Pangandaran dalam Meningkatan Keunggulan Kompetitif dan Preferensi Tamu - Cinky Priyanto; Apri Budianto; Aini Kusniawati (Jurnal Manajemen Bisnis Digital Terkini, 2024)
Jabarlink as an ISP (Internet Service Provider) company is known to be active in marketing JIMS (Jabarlink Internet Managed Service) products in the Pangandaran area, but still requires an ideal strategy to be able to market JIMS products which currently have positive potential for hotels that want to increase their competitive advantage and guest preferences. This research aims to design a marketing strategy for JIMS services in Pangandaran hotels to increase competitive advantage and guest preferences. A qualitative method with a descriptive approach has been used where data collection was carried out through interviews with 15 informants / hotel managers, and involving 100 hotel customers in the interview process using an online user questionnaire. This research found that ISP companies such as Jabarlink need to carry out three activities in their marketing process, namely: Product innovation to avoid the threat of substitute products, effective and creative communication, and market segmentation and offering the right price